Bentuk Penyajian Musik Gontong–Gontong Pada Acara Pernikahan Di Nagari Pasir Talang Kecamatan Sungai Pagu Kabupaten Solok Selatan - Arrithem Mosizi; Marzam Marzam (SENDRATASIK UNP, 2021)
This study aims to describe the presentation form of Gontong-gontong at wedding parties. This research belongs to a qualitative research using descriptive method. The main instrument in this research was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. The data were collected through observation, literature study, interview, and documentation. The data analysis was conducted by collecting the data, describing the data, and concluding the data. The results show that Gontong-Gontong is an art which is recognized by the community and is considered as an important element due to the fact that it was inherited by previous ancestors. Gontong-Gontong also provides entertainment for the community although Gontong-Gontong is only a media for Arak-Arakan at weddings. The presentation ofGontong-Gontong is carried out in the form of a band wagon at weddings. Gontong-Gontong is a medium for conveying messages to the public about the existence of a marker or event. The presentation of Gontong-Gontong can be found at wedding parties of Manjalang Mintuo procession.